Pessoas com deficiência organizando-se em cooperativas: uma alternativa de trabalho? - Carretta, Regina Yoneko Dakuzaku (Universidade Federal de São Carlos, 2004)
Co-operatives are been presented as an insertion alternative in trade work for disabled people, with different meaning from the most traditional proposals of leadings for formal jobs under Brazilian CLT (Consolidate Work Laws), in individual functions, in industrial activities, as the earlier proposal of professional rehabilitation models. On the other hand, the work co-operatives besides possibilities of work generation and profits are showed as a participative management and self-management in which there are social and economics goals. Nowadays, the work co-operative, specially the cooperative so named "popular" are been discussed and developed inside Solidary Economy, movement that search from solidary enterprises for an alternative to capital model of production. The popular co-operative involve socially excluded people, without economic sources and sometimes without both technical and professional knowledge which they might be able to develop economic activities like disabled people. With the main objective to know and evaluate the possibility of work cooperatives being able to include disabled people in work as well as to know the challenges and the outlooks, the present research proposed to develop case studies involving three kinds of enterprises. A lot of proposals and management were showed by analysed experiences, by showing the necessity of co-operative formation, challenges presented as a financial resources and technical capacitation, challenges in own participative management (hierarchy, involvement of co-operative workers in aggregative projects and challenges of owner management of choose economic activity (legalization, sources, diffusion, distribution of goods and trading). At last, the conclusion that co-operative management model could possible an alternative work/job generation and amounts to disabled people as well as, their participation and social inclusion. However, their building up there is no easy way and there are no handy formulas. There are a lot of challenges in collective and democratic management and by developing of own enterprise which confrontation involve not only technical meaning but both management and cultural capacitation.
Disabled people organizing in co-operatives: alternative for work?
Keywords: Cooperativas - organizações; Deficientes - trabalho; Economia solidária; Inclusão de deficientes; Disabled people; Work; Co-operatives; Solidary economy; Social inclusion; ENGENHARIAS::ENGENHARIA DE PRODUCAO